Ecosystem Services and River Basin Ecohydrology - Luis Chicharo (Springer, 2015)
This book provides an integrated analysis of the methodologies and main processes occurring at the entire river basin, from upstream until the coast, by merging the biological and hydrological processes with the social and economic components, thus providing an integrated framework for river basin management, integrating the ecohydrology approach with the ecosystem services concept.